Penerapan Diversi dan Restorative Justice dalam Kasus Penyalahgunaan Narkotika Anak: Kajian Yuridis - Moch. Ryan Saiful Bachri; Aturkian Laia (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Children's involvement in narcotics abuse in Indonesia places the Juvenile Criminal Justice System (Sistem Peradilan Pidana Anak/SPPA) at the intersection of child protection and narcotics law enforcement. This study aims to analyze the implementation of Diversion and Restorative Justice in resolving juvenile narcotics cases. It employs a normative juridical method using statutory and conceptual approaches by examining primary and secondary legal materials through prescriptive analysis. The findings reveal a lack of harmonization between the Juvenile Criminal Justice System Law and the Narcotics Law, particularly for offenses punishable by more than seven years' imprisonment, which limits the implementation of Diversion. Nevertheless, law enforcement officials remain obligated to pursue Diversion by prioritizing the best interests of the child. The application of Restorative Justice through rehabilitation, mediation, and reintegration into parental care provides a more recovery-oriented approach. Therefore, regulatory harmonization and strengthened institutional capacity are essential to ensure effective child protection and social reintegration.